The musicology of record production - Zagorski-Thomas, Simon (Cambridge University Press, 2014)
Recorded music is as different to live music as film is to theatre. In this book, Simon Zagorski-Thomas employs current theories from psychology and sociology to examine how recorded music is made and how we listen to it. Setting out a framework for the study of recorded music and record production, he explains how recorded music is fundamentally different to live performance, how record production influences our interpretation of musical meaning and how the various participants in the process interact with technology to produce recorded music. He combines ideas from the ecological approach to perception, embodied cognition and the social construction of technological systems to provide a summary of theoretical approaches that are applied to the sound of the music and the creative activity of production. A wide range of examples from Zagorski-Thomas's professional experience reveal these ideas in action
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Psychologie; Sound recordings / Production and direction / Philosophy and aesthetics; Sound recordings / Production and direction / Psychological aspects; Musical perception; Schallplattenproduktion